PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP KETEPATWAKTUAN PELAPORAN KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Ni Made Sunarsih; Ni Putu Shinta Dewi (JUIMA : JURNAL ILMU MANAJEMEN, 2019)
The purpose of this study is to determine the effect of audit commitee size, independence of audit commitee, competence of audit committee, level of committee audit education and frequency of audit committee meetings on the timeliness of nancial reporting. The reseach was conducted at banking company listed on the Indonesia stock exchange. The sampling method used purposive sampling, with a sample size of 35 company (105 observation). Data analysis used is multiple linear regression analysis. The results showed that independence of the audit committee, the competence of audit commitee and the frequency of audit committee meetings had negative effect on the timeliness of nancial reporting. While the audit committee size and level of committee audit education have no effect on the timeliness of nancial reporting.